Nuclear Abnormalities in Erythrocytes of Frogs from Wetlands and Croplands of Western Ghats Indicate Environmental Contaminations - Shreyas Raghunath; Chethankumar Masaruru Veerabhadrappa; Sannanegunda Venkatarama Bhatta Krishnamurthy (Journal of Tropical Life Science, 2017)
Anuran amphibians are the biological models to assess the influence of environmental contamination. We conducted nuclear abnormality assessment and micronuclei test in erythrocytes of frogs to identify an early influence of environmental contaminations. In Western Ghats of India, farmers use different agrochemicals and obviously, the amphibian habitat is contaminated with combinations of many residues. Many frog species use these agro-ecosystem for breeding and to complete early life stage. In the present study, we used Indian skipper frog (Euphlyctis cyanophlyctis (Anura: Ranidae)), a common inhabitant of water bodies in agro-ecosystems of Western Ghats for the assay. We collected the adult frogs from three different habitats; a) the rice paddy fields contaminated with agro-chemicals, b) uncontaminated marsh and c) a shallow water pool. We recorded micronucleus, blebbed, lobed, kidney bean shaped nucleus and nucleus with notches in erythro-cytes of these frogs. These nuclear abnormalities in erythrocytes are quantified. Â The incidences of occurrence of micronucleus ranged from 0 to 8 in 1000 analyzed cells. Â More than 80% of the frogs living in agro-chemical contaminated site showed these abnormalities. The appearance of nuclear abnormalities indicates that the frogs are affected by agro-chemicals.